Optimization of SMART-based PCR for amplification from picogram amounts of RNA. - Lin, Zhaoting. (2011)
One of the technical issues faced in malaria research involving transcriptional profiling and analysis using microarrays is the difficulty faced in obtaining adequate biological material from patients for field isolate studies. To overcome the problem, a SMART-based PCR technique is optimized to accurately amplify subnanograms of total RNA to yield dsCDNA for microarray hybridization and subsequent analyses. By varying conditions in both reverse transcription and polymerase chain reaction, the technique was optimized for total RNA input ranging from 300ng to 300pg, which equates to as low as 1560 cells required as starting material. The optimized conditions were capable of producing amplification products that not only provided good overall coverage of all probes and genes, but also generated good Pearson correlations above 0.80 when compared to amplification from 500ng, which served as a control. The number of genes which expressed at least three-fold change generally decreased with the amount of total RNA input used for amplification, suggesting that the relative abundance of differentially expressed genes is not as well maintained and becomes more variable when total RNA input approaches minute amounts.